All-optical relay-assisted FSO systems - Mohd Nor, Norhanis Aida; Ghassemlooy, Zabih; Komanec, Matej; Bohata, Jan; Zvanovec, Stanislav; Bhatnagar, Manav R.; Khalighi, Mohammad-Ali (Institution of Engineering & Technology (IET), 2019)
In this chapter, an all-optical FSO relay-assisted system is proposed to mitigate the destructive effects of the distance-dependent AT-induced fading. Relays are inserted directly in the link in order to reduce the AT-induced link loss, thus extending the link span and ensuring higher link availability as well as improving the overall system performance. Two all-optical relaying schemes are proposed and investigated, namely all-optical amplify-and-forward (AOAF) and all-optical regenerate-and-forward (AORF) FSO relay-assisted approaches. For the AOAF approach, the performance analysis of triple-hop AOAF FSO communications is done under the impact of nonhomogeneous atmospheric turbulence. The AORF relaying approach is then proposed to overcome the limitation imposed by AOAF system, where the signal and noise are accumulated at each relay, thus limiting the number of relay nodes that can be used